Knowledge Management System: Organizational Innovation as a Solution for Dispersed Work, Tacit and Common Knowledge - Anggraeni, Fadjar Setiyo (Yayasan Sinergi Kawula Muda, 2024)
When managed well, an organization's workforce's diversity of abilities may be a huge strategic advantage, fostering innovation and aiding in problem-solving abilities. Employers may encounter difficulties when employees work remotely and possess implicit knowledge. It is possible to transform seemingly ordinary knowledge into extraordinary knowledge when trustworthy management is in place. Using a qualitative descriptive method, this research attempts to examine the best knowledge management concepts, particularly those linked to tacit knowledge management. In order to obtain relevant and reliable results, we employ discourse analysis and narrative analysis procedures after accumulating data from literature, articles, and prior study notes using documentation techniques. This will also assist in developing the concept into a large, clear, and understandable thought. These results suggest that only in organizations with robust knowledge management systems can organizational innovation and issue solving take place. These results support the knowledge management hypothesis and offer further evidence that entrepreneurs can overcome the challenges posed by distant workers who possess tacit knowledge by maximizing knowledge management.